Pendampingan Guru TK PAUD dalam Pembuatan Media Pembelajaran Interaktif Berbasis Powtoon dan Microsoft Office Powerpoint - Tijaniyah Tijaniyah; Feri Febriyanto; Fahmi Dinillah (GUYUB: Journal of Community Engagement, 2021)
The Covid 19 pandemic period with community service in the form of training for PAUD kindergarten teachers in Paiton Probolinggo sub-district in making interactive learning media using powtoons and powerpoints is very useful to help teachers provide learning material online so that students don't get bored learning at home. The material is also varied and interactive which is useful to attract the enthusiasm of the students to study harder.